Design integration and analysis of nose dome for application of external pressure. (2021) - Anil Kumar Reddy, C.; KasiVaraprasada Rao, T.; Joshi, M.
Abstract: The design of any structure needs experimental evaluation before its use. In order to carry out the qualification of the structure, it is necessary to simulate the actual environment at a test facility. Under water vehicles are subjected to external pressure from the surrounding water. For every 10 m deep, there is an increase in pressure of 1 bar. The dome of an under-water vehicle protects the hardware and it experiences an approximate pressure of 25–35 bar at a particular point during its use. It is therefore necessary to qualify the dome for this pressure. To qualify the dome fixture has to be designed. Fixture design for this test involves design of a dome and test the dome section. Proper sealing and fastener arrangement has to be made. The design of the dome is integrated for reduction of thickness and to reduce the weight of dome as it should be lighter. The manufacturing process is also to be changed because the material should acquire good Mechanical properties to with stand the pressure. The best design and manufacturing process is to be selected to strive against the applied pressure.